Efektivitas model pembelajaran inquiry based learning dalam meningkatkan kemampuan berpikir kritis matematis siswa kelas X SMA - Gultom, Rosiana Claudia Br; Surya, Edy (Papanda Publisher, 2025)
Critical thinking skills are crucial as a basis for solving various problems in everyday life. A relatively weak critical thinking skill impacts students' understanding of learning materials, particularly in mathematics. This study aims to determine the effectiveness of the Inquiry Based Learning model in improving critical thinking skills of grade X high school students on quadratic functions and its effectiveness. This study is a quantitative study with a quasi-experimental approach. This study was conducted at Prayatna Private High School in Medan with a sample of 2 classes, each with 30 students. The research instrument used a critical thinking test in the form of essays. After the data were collected, data analysis was carried out using normality testing, homogeneity testing, hypothesis testing, and the N-Gain test. The results showed that there was a significant increase in students' critical thinking skills in the experimental class using Inquiry Based Learning. With these results, it can be concluded that the Inquiry Based Learning model is effective in improving critical thinking skills of grade X high school students in learning mathematics on quadratic functions. Therefore, the Inquiry Based Learning model is able to improve critical thinking skills in mathematics teaching.